Оцінка взаємозв’зків між інсулінорезистентністю, ендотеліальною дисфункцією, дисліпідемією, вмістом адипонектину і С-реактивного білка у хворих на цукровий діабет 2-го типу - Кехіопуло, Х. Ф. (Clinical Endocrinology and Endocrine Surgery, 2013)
Under a supervision there were 80 patients with type 2 diabetes mellitus (DM) in age from 41 to 74. It is set that for patients with newly diagnosed type 2 DM in combination with obesity there are hyperglycemia, hyperinsulinemia and insulin resistance (IR). Maximal hyperinsulinemia is marked at disease duration up to 5 years. At duration of disease the insulin secretion goes down from 6 to 10 years, and IR increases. For patients with newly diagnosed type 2 DM the atherogenic type IIb dyslipidemia was marked. Hypoadiponectinemia assists to IR development, forming the atherogenic lipid profile and endothelial dysfunction, bulge of intima-media complex. Between IR and endothelial dysfunction from data of correlation analysis there is high positive connection that increases with the increase of DM duration for women. By principal reasons of endothelial dysfunction the type 2 DM patients during the moment of diagnosis have a chronic hyperglycemia, IR, dyslipidemia, hypoadiponectiemia, vascular inflammation.